An approach to accurate computed tomography imaging interpretation in penetrating neck trauma. (June 2020) - Adams, Ashok; Shah, Nimesh; Stephenson, Rob
Penetrating neck injury can have potentially devastating consequences due to the many vital structures contained within the neck. In patients who do not require immediate surgery, computed tomography angiography of the neck is the test of choice to characterize the injury. A systematic approach to assessment will ensure a thorough evaluation and give the reporting radiologist the best chance of identifying the significant findings, which can often be subtle. Clear communication with the trauma team at both the time of request and after the imaging has been evaluated to relay any significant findings is vital to ensure the best outcome for the patient.